Pregnancy complications after liver transplantation. Issue 1 (January 2015) - Jabiry-Zieniewicz, Zoulikha; Dabrowski, Filip A.; Pietrzak, Bronislawa; Wielgos, Miroslaw
Abstract Objective To review complications in pregnancy after liver transplantation and assess the time interval since transplantation on fetal development and preterm birth rate. Method A retrospective review of 53 pregnancies after liver transplantation among 45 women who delivered at the Medical University of Warsaw between 2001 and 2013. Results Mean duration of pregnancy was 37 ± 2.3 weeks. Main complications were liver dysfunction, small-for-gestational-age, and preterm delivery. Mean time from transplant to pregnancy was 54 ± 36 months for women who delivered before 34 weeks (n = 9), 42 ± 43 months for delivery at 34 − 36 weeks (n = 10), and 57 ± 36 months for delivery after 37 weeks. Mean neonatal weight was 2838 ± 626 g (< 34 weeks, 1897 ± 382 g; 34 − 36, 2324 ± 330 g; > 37, 3125 ± 474 g). Fourteen (26%) neonates had low birth weight (< 2500 g) and 30 (56%) weighed < 3000 g. Pregnancy proceeded without complication in 13 (29%), with a mean time from transplantation to conception of 52 months. Conclusion Although physiological gestation and delivery at term are possible for women after liver transplantation, pregnancy is considered high risk. Counselling before pregnancy is required and patients must be managed by an obstetrician and a hepatologist.